2019
DOI: 10.1055/s-0039-1692481
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Pain and Predictors of Pain Relief after Ulnar Shortening Osteotomy for Ulnar Impaction Syndrome

Abstract: Background The purpose of this study is to characterize patient- and surgery-specific factors associated with perioperative pain level in patients undergoing ulnar shortening osteotomy (USO) for ulnar impaction syndrome (UIS). We hypothesize that preoperative opiate consumption, tobacco utilization, and severity of ulnar variance will be associated with less postoperative pain relief. Methods All cases of USO between January 2010 and December 2016 for management of UIS were retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(42 reference statements)
3
1
0
Order By: Relevance
“…This was also previously reported by Nunez et al. [ 43 ]. Based on our findings, there is no need to inform patients differently based on the etiology of UIS regarding potential pain relief and gain of function after USO.…”
Section: Discussionsupporting
confidence: 90%
“…This was also previously reported by Nunez et al. [ 43 ]. Based on our findings, there is no need to inform patients differently based on the etiology of UIS regarding potential pain relief and gain of function after USO.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous studies focusing on USO for UIS. 8,[32][33][34] As shown in our study, ulnar variance improved with USO in previous literature. 8,33,34 This review showed a trend toward less ulnar variance change from baseline in metaphyseal curved technique in comparison with diaphyseal techniques, especially the oblique diaphyseal surgical technique.…”
Section: Comparison With the Literaturesupporting
confidence: 84%
“…8,[32][33][34] As shown in our study, ulnar variance improved with USO in previous literature. 8,33,34 This review showed a trend toward less ulnar variance change from baseline in metaphyseal curved technique in comparison with diaphyseal techniques, especially the oblique diaphyseal surgical technique. This is in contrast to the study by Marquez-Lara et al 32 where metaphyseal USO showed a larger change from baseline.…”
Section: Comparison With the Literaturesupporting
confidence: 84%
“…Conservative treatment can only temporarily relieve wrist pain but cannot be treated thoroughly. The key to the treatment of this disease is to accurately and effectively reduce the ulnar positive variation and restore the wrist's anatomical structure 4 . Therefore, surgery is still the main treatment for UIS.…”
Section: Introductionmentioning
confidence: 99%